2020
DOI: 10.1007/s00221-019-05714-9
|View full text |Cite
|
Sign up to set email alerts
|

Motor congruency and multisensory integration jointly facilitate visual information processing before movement execution

Abstract: Attention allows us to select important sensory information and enhances sensory information processing. Attention and our motor system are tightly coupled: attention is shifted to the target location before a goal-directed eye-or hand movement is executed. Congruent eye-hand movements to the same target can boost the effect of this pre-movement shift of attention. Moreover, visual information processing can be enhanced by, for example, auditory input presented in spatial and temporal proximity of visual input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Motor executions were valid (i.e., all end points were closer to the target than a distractor location, and movements had amplitudes of more than two visual degrees and onsets after probe offsets) in 58.3% ( SD = 15.4%) of all trials on average. This percentage is comparable to previous studies ( Khan et al, 2011 ; Elshout, Van der Stoep, Nijboer, & Van der Stigchel, 2020 ) and not surprising given the difficulty of the task. Nonetheless, we kept invalid trials for analyses for the sake of statistical power and because an inaccurate motor execution does not necessarily mean that the shift of attention was inaccurate.…”
Section: Resultssupporting
confidence: 90%
“…Motor executions were valid (i.e., all end points were closer to the target than a distractor location, and movements had amplitudes of more than two visual degrees and onsets after probe offsets) in 58.3% ( SD = 15.4%) of all trials on average. This percentage is comparable to previous studies ( Khan et al, 2011 ; Elshout, Van der Stoep, Nijboer, & Van der Stigchel, 2020 ) and not surprising given the difficulty of the task. Nonetheless, we kept invalid trials for analyses for the sake of statistical power and because an inaccurate motor execution does not necessarily mean that the shift of attention was inaccurate.…”
Section: Resultssupporting
confidence: 90%
“…The two principles that have been suggested as a driven for multisensory integration are spatial [3], [4], and temporal congruency [5], [6]. For example, when a light and a sound are originated in a temporal and spatial binding window (i.e., close in time and location), it is likely that both stimuli will be integrated into a unified percept [7]. Multisensory cues can be particularly used to infer spatiotemporal features of an external event.…”
Section: Introductionmentioning
confidence: 99%
“…However, motor action is not simply a measure of perception, as both processes are tightly coupled being both influenced by each other. It has been suggested that multisensory integration and motor system lead to enhanced sensory processing [7]. In this line, Valzolgher and collaborators (2020) suggested that, when updating auditory spatial localization, kinesthetic cues have an added value to just paying attention to seeing and/or hearing sounds' positions [13].…”
Section: Introductionmentioning
confidence: 99%